1941
DOI: 10.1136/bmj.2.4213.486
|View full text |Cite
|
Sign up to set email alerts
|

War Conditions and the Mental Health of the Child

Abstract: Last February Miss Dunsdon, our psychologist, made a survey of 8,000 Bristol school children to assess the incidence of strain following air raids. Her findings were that about 4°,b of this large sample of the school population showed some signs of strain, either purely psychological or else psychosomatic. Among the psychological symptoms noted were general nervousness, trembling, crying, and aggressive behaviour. Among the psychosomatic symptoms were headaches, anorexia, indigestion, enuresis, soiling, pallor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 0 publications
2
18
0
Order By: Relevance
“…Both groups may, therefore, have performed at a significandy lower level on cognitive and language tests and exhibited more behavioral symptoms than would Eritrean children growing up with their families under peace time conditions. The greater prevalence of deviant behavior among orphans than refugee children is consistent with the hypothesis that permanent separation from both parents at an early age has a distinctly negative effect on social-emotional development (Bodman, 1941;Bowlby, 1980;Crook 8c Eliot, 1980). The fmding that the youngest orphans in the group showed relatively more behavioral symptoms and were less advanced than older orphans relative to refugee children on cognitive measures is also consistent with the hypothesis that younger children are somewhat more vulnerable to psychological stress and deprivation than older children (Garmezy &: Rutter, 1985;Jensen Sc Shaw, 1993;Lyons, 1987).…”
Section: Discussionsupporting
confidence: 78%
“…Both groups may, therefore, have performed at a significandy lower level on cognitive and language tests and exhibited more behavioral symptoms than would Eritrean children growing up with their families under peace time conditions. The greater prevalence of deviant behavior among orphans than refugee children is consistent with the hypothesis that permanent separation from both parents at an early age has a distinctly negative effect on social-emotional development (Bodman, 1941;Bowlby, 1980;Crook 8c Eliot, 1980). The fmding that the youngest orphans in the group showed relatively more behavioral symptoms and were less advanced than older orphans relative to refugee children on cognitive measures is also consistent with the hypothesis that younger children are somewhat more vulnerable to psychological stress and deprivation than older children (Garmezy &: Rutter, 1985;Jensen Sc Shaw, 1993;Lyons, 1987).…”
Section: Discussionsupporting
confidence: 78%
“…Bodman (1941) described the experience of 44 children who were being treated at a hospital when a bomb exploded. For the older children, the event was retold much like one recalls an adventure.…”
Section: Protective Factors and Resiliencementioning
confidence: 99%
“…Reports of children's reactions to air raids during World War 11 indicated that although there were many emotional casualties, children of all ages showed a capacity to "take it" which confounded predictions that bombing and evacuations would make nervous wrecks of a large proportion of them (Bodman, 1941;John, 1941;Vernon, 1941;Freud 8~ Burlingham, 1944). There was a strong suggestion that some of the worst effects on children could have resulted from observing the reactions of over-anxious and hysterical adults.…”
Section: Gordon Milne University Of Queenslandmentioning
confidence: 99%